The art of writing: Disguise and recognition in Nelly Richard's Avanzada. Issue 2 (2015) - Vodanovic, Lucia
Abstract : Now that different publications and exhibitions have started to revisit the history of art produced in Chile during the dictatorship of General Pinochet (particularly that of the Escena de avanzada ), this article examines the critical role of Nelly Richard's practice of writing as an attempt to constitute the avanzada ex nihilo and to resist state repression through its paradoxical coupling of disguise and recognition. By discussing key texts from Richard's corpus of work, and paying attention to their engagement with different artworks during this period, the article suggests that her writing embodies a programmatic strategy of dissidence and disruption and a desire to transform the hierarchical military coup into a horizontal scene in which established meanings are blown apart and re-inscribed.